Adaptasi Riparian di Sekitar Sungai Tabobo Dusun Beringin Halmahera Utara: Tinjauan Fitoremediasi Pada Sungai Terindikasi Cemar - Muhlis Mukaram; Zulkifli Ahmad; Retno Peni Sancayaningsih (Biogenesis: Jurnal Ilmiah Biologi, 2015)
The Illegally Gold Mining Activities (PETI), which exacerbated to the water conditions of the Tabobo river. One of the higher problems for the people around PETI area was the use heavy metal mercury (Hg). The purpose of this study was to determine the abundance of the plants that  adaptable to the environtmental condition and to analyze concentration of mercury (Hg) absorbed by riparian vegetation of Tabobo and Kao river, Malifut and Kao regencies, North Halmahera. Three rivers were selected, two of them represented the high intensity of gold mining, Tabobo and Kao rivers, and Umbul Nilo water spring output at Margosuko, Daleman village, Klaten subregency as a control area. In each station were placed six square plots (1 x 1 m2 size) located in the upstream, midstream, and the down-stream of the selected river sites. The mercury content absorbed by dominant plants samples was analyzed using Mercury Analyzer after wet destruction. The research results showed that Poaceaae, Commelinaceae, and Convolvulaceae were found both inTabobo and Nilo river, especially Digitaria and Commelina genera, while Panicum and Paspalum were only found in 2 polluted rivers, Tabobo and Kao. These assumed that they function as plant accumulator. The mercury content in the leaves of Paspalum sp. both in upstream and midstream of Tabobo river, has lower value compared to the standard (<0.01 ppb), but in the downstream showed that mercury level absorbed by Paspalum sp. leaves was high (11.57 ppb). Mercury levels of Macaranga sp. leaves tree in Beringin village had the value of the 36.45 ppb. On the contrary, mercury analysis of Panicum repens L. leaves representing floor vegetation, and leaves of Macaranga semiglobosa J.J.S. surrounding Kao river showed that the mercury contents were below the threshold value (<0.01 ppb).Keywords: adaptation, fitoremediation, Halmahera Utara, Riparian, Tabobo